Validation of the Malay version of the Inventory of Callous-Unemotional traits (ICU) among adolescents in Pahang - Khalil, Aref Ezrin Mohamad (2021)
Background: One of the key components in the study of antisocial behavior among adolescents is the presence of callous-unemotional (CU) traits. Among the most established tools available to measure CU traits is the Inventory of Callous-Unemotional traits (ICU). To date, information regarding the psychometric properties of this scale when used in the local context is still lacking. Therefore, there is a need to validate the Malay version of the ICU so that research can be conducted to explore on CU traits among adolescents in Malaysia and their associated factors. Objectives: The aim of the study is to validate the Malay version of the Inventory of Callous-Unemotional Traits (M-ICU) Methodology: A cross-sectional study involving 409 adolescents aged between 13 to 18 years old was conducted from August 2020 until October 2020 in six secondary schools in the district of Kuantan, selected via multistage random sampling method. M-ICU was initially translated into Malay using forward and backward translation procedure by a group of experts. The final version of the M-ICU was harmonized and pre-tested on 10 participants. Study participants who assented for the study and obtained parental consent then completed the final version of the M-ICU questionnaire and a socio-demographic questionnaire. Data was analysed using SPSS version 26 and MPlus software for construct validity by performing exploratory factor analysis, confirmatory factor analysis and construct reliability. Results: In this study, initial EFA revealed three factors with two items deleted. EFA was then repeated with two factors resulting in the deletion of items from the Unemotional factor. Cronbach alpha for overall scale improved from 0.70 to 0.74 while alpha for Uncaring and Callousness factor was 0.790 and 0.674 respectively. After CFA, the final model of the M-ICU that provided best fit to the data comprised of two factors with 17 items, compared to the original English version that has three factors with 24 items. The findings revealed acceptable fit indices (RMSEA=0.057, CFI=0.941, TLI=0.932, WRMR= 0.968). Conclusion: The study revealed that a two-factor model with 17 items of the Malay Version of M-ICU has good psychometric properties. The scale is valid and reliable to measure callous and unemotional traits among adolescents in Malaysia.